Experimental Study and ANFIS Modeling for Scour Behind Al-Shamiya Barrage - Razzak Al-Husseini, Thulfikar; Janna, Hussein; M. Hamza, Walaa (International Journal of Engineering and Technology, 2018)
Generally, the scour behind hydraulic structures considered as an important matter the may be lead to failure. So, in this paper an experimental study and ANFIS modeling for a selected case study which is Al-Shamiya Barrage in Iraq. The M-9 device and GIS technique were used for collecting the data from field. The collection of data started from 1/12/2016 until to 1/3/2017 with monthly observation. A grid of (10 × 10) m for the 40 m length behind the floor of barrage was used to collect the experimental data. Furthermore, samples of sand from bed in that region were collected in order to implement the sieve analysis to specify the d50 and then to specify the Manning coefficient. Some equations used to calculate depth of scour behind the barrage. Then the data obtained was divided randomly into two parts: 80 % for training and 20 % for testing the model to implement the model by using ANFIS technique. The ANFIS model gave RMSE equal to 3.3965 × 10-6 m for training and 0.273 m for testing the model, respectively. This study concluded that the scour behind Al-Shamiya Barrage was clear experimentally using M-9 device and can be modeled using ANFIS model.
Keywords: Al- Shamiya Barrage; ANFIS model; Hydraulic structure; M-9 device; Scour.